Perceived Usefulness, Tagline, Brand Image And Their Impact On The Society Of Palembang City On Repurchase Decisions Of Products In Lazada E-Commerce Through Customer Satisfaction As An Intervening Variable And Its Study From The Perspective Of Sharia Economics - Yelisa Juliarti; Mismiwati; Chandra Zaky Maulana (CV. Doki Course and Training, 2025)
This study aims to analyze the influence of perceived usefulness, tagline, brand image, and their impact on the society of Palembang City on repurchase decisions of products in Lazada e-commerce through customer satisfaction as an intervening variable within the perspective of Sharia economics. The study applies a quantitative approach. The population consists of Palembang City residents who use Lazada e-commerce, with a total sample of 100 respondents. Primary data were collected through questionnaires using a Likert scale and interviews. The data analysis techniques employed include the outer model, inner model, hypothesis testing, and intervening effect testing. The results indicate that: (1) perceived usefulness, tagline, and brand image have a positive and significant direct effect on product repurchase decisions; (2) perceived usefulness, tagline, and brand image positively and significantly affect customer satisfaction; (3) customer satisfaction has a positive and significant effect on repurchase decisions; and (4) customer satisfaction is able to mediate the effect of perceived usefulness, tagline, and brand image on repurchase decisions. From the perspective of Sharia economics, consumption should be based on a balance between needs and capabilities, avoid excessiveness, choose products that are halal, good, and beneficial, do not cause harm, and be carried out with honesty and prudence, so that repurchase decisions reflect responsible consumption behavior aligned with Islamic values.